Work-life balance e o trabalho docente: um estudo nos programas de pós-graduação stricto sensu em ciências contábeis no Brasil - Costa, Laura Brandão (2018)
The balance between work and family, in other words, the work-life balance, is characterized by two natures: the conflict and the positive interface. Although most studies present the work-life balance in a negative or conflicting way, it is known that well-being in one domain, work or family, benefits the other domain. Considering both natures of balance, the objective of this study was to investigate the relationship between the conflict variables and the positive interface between work and family with the work-life balance of teachers who work in the stricto sensu post-graduate programs in Brazilian Accounting Sciences, discussing how conflicts or their non-existence affects the borders between both domains. The Work-Family Conflict Scales and Positive Interface Scale between Work and Family, both adapted and in Brazil, validated by Aguiar (2016), were applied as a tool for data collection, applied to a sample of 136 (one hundred and thirty-six) teachers. The socio-demographic profile, occupational and family, of the sample showed, mostly, male teachers, married, with children and who also share the financial responsibility for the maintenance of the family. The multivariate modeling technique of structural equations was performed to identify the inexistence or existence of conflicts and the positive interface in the work-family relationship and verify the variables could be related to both natures, since the conflict and the positive interface are manifested by (work-family and work-family) and the multidimensional nature of time, stain and behavior (in the case of conflict) and dimensions of enrichment, positive spillover, facilitation and valorization (in the case of the positive interface). The results pointed out the existence of both conflicts and the positive interface in the work-life balance teacher, with predominance of the positive interface. Variables characterizing the time and tension dimensions were related to the conflict between work and family, reinforced by teachers' reports. It was also verified that enrichment, spillover positive and valorization variables related to the positive interface, also emphasized by the report of the teachers who affirmed to obtain experiences and develop skills in one domain, which favor their performance in the other. Regarding socio-demographic variables, only gender showed a statistically significant association with the conflict. The results, analyzed in the light of the Work/Family Border Theory, point out that the physical, temporal and psychological borders that the teachers shape around work and family are permeable and flexible, since their professional activities interfere in the execution of their family roles. Teachers consider that the profession distracts them from the family (degree of association: 0,827), since the physical and temporal borders, due to their permeability and flexibility, lead them to carry out teaching tasks in a family environment, depriving them of more time for family reunion. It was also confirmed that support and well-being in the family environment improves the teachers' mood in the professional environment (degree of association: 0,928), pointing out that the enrichment promoted by family involvement promotes a sense of focus that helps them to be better at work. The psychological borderline is also flexible and admits the permeability of family feelings and behaviors at work. The frontiers facing the work and family domains are therefore permeable and flexible, expanding as necessary from the perspective of the conflicting or positive nature of the work-life balance.